Boroxine benzaldehyde complex for pharmaceutical applications probed by electron interactions. (10th November 2022) - Pereira‐da‐Silva, Joao; Nunes, Ana; Mendes, Monica; Rodrigues, Rodrigo; Cornetta, Lucas; Ferreira da Silva, Filipe
Abstract : Rationale: 2, 4, 6‐Tris(4‐formylphenyl)boroxine (TFPB) is a substituted boroxine containing a benzaldehyde molecule bonded to each boron atom. Boroxine cages are an emerging class of functional nanostructures used in host–guest chemistry, and benzaldehyde is a potential radiosensitizer. Reactions initiated by low‐energy electrons with such complexes may dictate and bring new fundamental knowledge for biomedical and pharmaceutical applications. Methods: The electron ionization properties of TFPB are investigated using a gas‐phase electron–molecule crossed beam apparatus coupled with a reflectron time‐of‐flight mass spectrometer in an orthogonal geometry. Ionization and threshold energies are experimentally determined by mass spectra acquisition as a function of the electron energy. Results: The abundance of the molecular precursor cation in the mass spectrum at 70 eV is significantly lower than that of the most abundant fragment C7 H5 O + . Twenty‐nine cationic fragments with relative intensities >2% are detected and identified. The appearance energies of six fragment cations are reported, and the experimental first ionization potential is found at 9.46 ± 0.11 eV. Moreover, eight double cations are identified. The present results are supported by quantum chemical calculations based on bound state techniques, electron ionization models and thermodynamic thresholds. Conclusions: According to these results, the TPFB properties may combine the potential radiosensitizer effect of benzaldehyde with the stability of the boroxine ring.